First record of Unguiculariopsis ravenelii (Leotiomycetes, Ascomycota) from Mexico - Raymundo, Tania; Martínez-Pineda, Michelle; Cobos-Villagrán, Aurora; Sánchez-Flores, Marcos; Valenzuela, Ricardo (Instituto de Ecología, A.C., 2020)
Background and Aims: The genus Unguiculariopsis of the class Leotimycetes within Ascomycota is characterized by forming inconspicuous apothecia up to 2 mm in diameter, with hook-shaped hairs on the external surface, inoperculate and inamyloid asci, and globose, subglobose to ellipsoid ascospores, which are hyaline with guttules. They are fungicolous fungi which are host-specific. The objective of this study is to report Unguiculariopsis ravenelii for the first time in Mexico.Methods: The specimens studied are deposited in the ENCB herbarium of the Instituto Politécnico Nacional, Mexico. The material was reviewed in fresh and dry, and described macromorphologically using a stereomicroscope, based on pictures taken in situ, and micromorphological characters with an optical microscope. They were identified with specialized keys and literature.Key results: The description of Unguiculariopsis ravenelii of Mexico is presented. This is a species characterized by being mycoparasite and forming gregarious apothecia growing on Rhytidhysteron rufulum.Conclusions: This species is distributed in tropical dry forest and produces its sporomas during the rainy season in the states of Colima, Jalisco, Nayarit, Oaxaca, Puebla, Sonora, Tabasco and Tamaulipas in the Neotropical region of Mexico.